Glycerin Removal from Ultrafiltration Flat Sheet Membranes by Filtration and Soaking - Arénillas, Sophie; Drouin, Maryse; Monnin, Emmanuel; Moulin, Philippe (Journal of membrane science and research, 2017)
In the case of pharmaceutical processes, the presence of preservatives can be problematic and the quantity is subject to stringent standards. So, the aim of this study is to quantify the removal of glycerin contained in ultrafiltration flat sheet membranes by filtration and soaking. This is carried out over a wide range of membranes with different characteristics. The selected flat sheet membranes (with a surface of 14.5 cm²) have a Molecular Weight Cut-Off (MWCO) ranging from 5 to 60 kDa. They are made of different organic materials (polyethersulfone, regenerated cellulose and etc.) and are manufactured by different suppliers (Millipore, Sartorius, GE Osmonics, Novasep, Pall). The density and therefore the glycerin concentration measurements are carried out in filtered distilled water (dead-end filtration) and distilled water of soaking (diffusion phenomenon). This study gives experi-mental information about the glycerin quantity as a function of membrane characteristics and the position of glycerin on the membrane (skin layer and support). The various studied parameters are the removal kinetic, the filtered volume, the filtration pressure and the contact time.